Conventional and Unconventional Antimicrobials from Fish, Marine Invertebrates and Micro-algae - Smith, Valerie J. (Molecular Diversity Preservation International, 2010)
All eukaryotic organisms, single-celled or multi-cellular, produce a diverse array of natural anti-infective agents that, in addition to conventional antimicrobial peptides, also include proteins and other molecules often not regarded as part of the innate defences. Examples range from histones, fatty acids, and other structural components of cells to pigments and regulatory proteins. These probably represent very ancient defence factors that have been re-used in new ways during evolution. This review discusses the nature, biological role in host protection and potential biotechnological uses of some of these compounds, focusing on those from fish, marine invertebrates and marine micro-algae.